Keats, Incorporated: Social Authorship and the Making of a Brand. Issue 2 (4th March 2022) - Gamer, Michael; Parker, Deven
ABSTRACT: Our essay extends recent criticism—that challenges the notion of Keats as a solitary genius unengaged with social life and politics—to the realms of literary marketing and bookmaking. Keats, we argue, was anything but uninterested in the business of literature, let alone irreparably wounded by savage treatment in the press. Our essay thus asks how Endymion 's reception informed Keats's and his circle's preparation of Lamia, Isabella, The Eve of St. Agnes, and Other Poems for the press. "Keats Incorporated" presents a practical-minded Keats who, with his team of editors and publishers, sought to market "the Author of Endymion " to audiences tired of partisan reviewing practices. Examining the 1820 volume's ordering of poems, newspaper advertisements, letters between members of Keats's team, and understudied paratexts from all three of Keats's published books, we show how the Lamia volume constructs a marketable authorial persona—one that emerges from that earlier maligned volume.